Once upon a book - Lin, Grace; Messner, Kate (Little, Brown and Company, 2023)
"Alice can go anywhere in the magical pages of her favorite book. So when it flaps its pages and invites her in, she is swept away to a world of wonder and adventure. But at the end of her imaginative journey, she yearns for the place she loves best of all."--